The Digital Financial Literacy and FinTech in Green Finance Adoption among MSMEs in South Sumatra - Purnamasari, Endah Dewi; Marcelina, Dona; John Roni Coyanda; Audia Stephani Syahputri; Sarah Haryani (Jurnal Ilmiah Ekonomi Global Masa Kini, 2025)
This study aims to analyze the influence of digital financial literacy and financial technology on the implementation of green finance among Micro, Small, and Medium Enterprises (MSMEs) in South Sumatra Province. The research employed a quantitative approach using a survey method by distributing questionnaires to 150 MSME actors across eight districts and cities. Data were analyzed through validity, reliability, classical assumption tests, and multiple linear regression analysis. The results indicate that digital financial literacy has a positive and significant effect on the implementation of green finance. MSME actors with a high level of digital literacy are better able to utilize technology-based financial services to manage their businesses efficiently and in an environmentally sustainable manner. In addition, financial technology also shows a positive and significant influence on green finance implementation, reflecting that the use of FinTech enhances transaction efficiency, transparency, and access to green financing for MSMEs. The coefficient of determination (R²) value of 0.648 indicates that digital financial literacy and financial technology jointly explain 64.8% of the variation in green finance implementation. These findings suggest that improving digital financial literacy and adopting financial technology are key factors in promoting the implementation of green finance and enhancing MSME performance to become more adaptive to the dynamics of the digital economy. Keywords: Digital Financial Literacy, Financial Technology, Green Finance, MSMEs.